Simulation of vertical handover algorithms with NCTUns (2010)
This paper presents the simulation of Vertical Handover Algorithms (VHA) using NCTUns and tested them on scenarios with WiFi/GPRS or WiFi/WiMAX Mobile networks: The first evaluates parameters such as the network bandwidth, economic cost of the connection and the mobile node mobility and uses a cost function toevaluate candidate networks. The second one is based on application requirements such as bandwidth, latency and % packet loss rate. The third one organizes the nodes connections to balance the load on connection points, optimize battery consumption, or both. We developed several scripts in C and PERL language for inclusion in the tool like other components and use a NCTUns API to communicate with the simulation engine. In simulation scenario we use the multi-interface node for Intelligent Transportation System (ITS) networks or a node for each technology, but they behave as a single node with multiple interfaces. Simulations results are used to analyze the VHAs performance measuring handover delay, number of avoided handovers and computational cost of the algorithms.